(3eMGceGJ edG LdGd dCMeO Hf MjOQ GdcQOis - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s ((3CMeO Hf EHQGgje s)
(3ChdgG (B:s
(3hHYO agPg JYdjbGJ Hd JfHjgGJ Ydi JMbjbGJ eNJajI ai UaMGJ TQM GdYbGFO GdYVOjI ddYdGeI eMeO Hf CSYO GdUOjbi GdOhGfi s
(3BNQgG (B:s
(3hEfeG ge TjYI EHdjS ESJhdi Ydi Ybhdge hCVdge VdGdkG HYjOkG bGJdge Gddg hbO NJe GdcJGH HYhf Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds